Exceptional plasticity in the bulk single-crystalline van der Waals semiconductor InSe - Wei, Tian-Ran; Jin, Min; Wang, Yuecun; Chen, Hongyi; Gao, Zhiqiang; Zhao, Kunpeng; Qiu, Pengfei; Shan, Zhiwei; Jiang, Jun; Li, Rongbin; Chen, Lidong; He, Jian; et al. (Science (American Association for the Advancement of Science), 2020)
Inorganic semiconductors are vital for a number of critical applications but are almost universally brittle. Here, we report the superplastic deformability of indium selenide (InSe). Bulk single-crystalline InSe can be compressed by orders of magnitude and morphed into a Möbius strip or a simple origami at room temperature. The exceptional plasticity of this two-dimensional van der Waals inorganic semiconductor is attributed to the interlayer gliding and cross-layer dislocation slip that are mediated by the long-range In-Se Coulomb interaction across the van der Waals gap and soft intralayer In-Se bonding. We propose a combinatory deformability indicator (Ξ) to prescreen candidate bulk semiconductors for use in next-generation deformable or flexible electronics.Inorganic semiconductors are vital for a number of critical applications but are almost universally brittle. Here, we report the superplastic deformability of indium selenide (InSe). Bulk single-crystalline InSe can be compressed by orders of magnitude and morphed into a Möbius strip or a simple origami at room temperature. The exceptional plasticity of this two-dimensional van der Waals inorganic semiconductor is attributed to the interlayer gliding and cross-layer dislocation slip that are mediated by the long-range In-Se Coulomb interaction across the van der Waals gap and soft intralayer In-Se bonding. We propose a combinatory deformability indicator (Ξ) to prescreen candidate bulk semiconductors for use in next-generation deformable or flexible electronics.